The Implementation of a Multidisciplinary Approach for Potential Organ Donors in the Emergency Department. Issue 11 (November 2019) - Witjes, Marloes; Kotsopoulos, Angela M.M.; Otterspoor, Luuk; Herold, Ingeborg H.F.; Simons, Koen S.; Woittiez, Karen; Eijkenboom, Jos J.A.; van der Hoeven, Johannes G.; Jansen, Nichon E.; Farid Abdo, Wilson
Abstract : Background: The aim of this study was to evaluate the implementation process of a multidisciplinary approach for potential organ donors in the emergency department (ED) in order to incorporate organ donation into their end-of-life care plans. Methods: A new multidisciplinary approach was implemented in 6 hospitals in The Netherlands between January 2016 and January 2018. The approach was introduced during staff meetings in the ED, intensive care unit (ICU), and neurology department. When patients with a devastating brain injury had a futile prognosis in the ED, without contraindications for organ donation, an ICU admission was considered. Every ICU admission to incorporate organ donation into end-of-life care was systematically evaluated with the involved physicians using a standardized questionnaire. Results: In total, 55 potential organ donors were admitted to the ICU to incorporate organ donation into end-of-life care. Twenty-seven families consented to donation and 20 successful organ donations were performed. Twenty-nine percent of the total pool of organ donors in these hospitals were admitted to the ICU for organ donation. Conclusions: Patients with a devastating brain injury and futile medical prognosis in the ED are an important proportion of the total number of donors. The implementation of a multidisciplinary approach is feasible and could lead to better identification of potential donors in the ED. Abstract : Supplemental Digital Content is available in the text.